Procedural Justice, Attitudes, and Subsidiary Top Management Compliance with Multinationals' Corporate Strategic Decisions - Kim, W. Chan; Mauborgne, Renée (Academy of Management Journal, 1993)
This study concerned strategy implementation in multinational organizations. In previous research, subsidiary top managers' perception that their head offices exercised procedural justice positively affected the former's commitment, trust, and outcome satisfaction. Here, we traced the effect of procedural justice beyond attitudes to the behavior of compliance. Results, based on two-stage longitudinal data, suggest that procedural justice enhances subsidiary top managers' compliance directly and indirectly, through the attitudes of commitment, trust, and outcome satisfaction. These effects were not, however, constant but were more powerful for managers of subsidiaries operating in global, as opposed to multidomestic, industries.